Association between pet ownership and coronary artery disease in a Chinese population. Issue 13 (March 2017) - Xie, Zhi-Yong; Zhao, Di; Chen, Bing-Rui; Wang, You-Nan; Ma, Yao; Shi, Hao-Jie; Yang, Yang; Wang, Ze-Mu; Wang, Lian-Sheng
Abstract : Abstract: A number of studies have suggested the benefits of pet ownership to human health, including cardiovascular disease (CVD). However, there are few findings regarding pet ownership and coronary artery disease (CAD). The objective of this study is to investigate the association between pet ownership and CAD in a Chinese population. From October 2015 to May 2016, a survey consisting of 561 consecutive patients was done in Nanjing, China. Based on the results of coronary arteriography for the first time, participants were divided into 2 groups (non-CAD and CAD groups). Pet ownership information was collected by using a questionnaire. After multivariate adjustments, pet ownership was associated with a decreased CAD risk (odds ratios [OR]: 0.504, 95% confidence intervals [CIs]: 0.310–0.819). There was a reduced CAD risk among dog owners (OR: 0.420, 95% CI: 0.242–0.728) when compared with the cat group (OR: 0.738, 95% CI: 0.240–2.266) and the cat and dog group (OR: 1.052, 95% CI: 0.330–3.355). With the increase of pet ownership duration, there was a decreased tendency of CAD risk, including years of keeping pets ( P for trend = 0.008) and time of playing with pets per day ( P for trend = 0.001). In addition, similar dose–response relationship was observed for starting age of keeping pets ( P for trend = 0.002). Pet ownership, especially dog ownership, can be a protective factor for CAD in Chinese patients.